Dehydroepiandrosterone supplementation for poor-responder IVF patients: is it promising?. (March 2011) - Kahraman, Korhan; Söönmezer, Murat
Evaluation of: Wiser A, Gonen O, Ghetler Y, Shavit T, Berkovitz A, Shulman A. Addition of dehydroepiandrosterone (DHEA) for poor-responder patients before and during IVF treatment improves the pregnancy rate: a randomized prospective study. Hum. Reprod. 25(10), 2496––2500 (2010). Management of poor-responder patients still remains among the foremost challenging issues in reproductive medicine. Albeit with limited success, various strategies have been practiced to overcome this problem. In some preliminary reports, the use of dehydroepiandrosterone prior to controlled ovarian stimulation regimens, which is proposed to act as a steroid prehormone for ovarian follicular sex steroidogenesis, has been suggested as an alternative strategy for the treatment of poor-responder patients. Recently, a randomized controlled trial has also supported these preliminary results.